EVALUASI SISTEM DAN PROSEDUR UANG PERSEDIAAN (UP) PADA DINAS LINGKUNGAN HIDUP DAERAH PROVINSI SULAWESI UTARA - Pasuhuk, Fita Helena; Kalangi, Lintje; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
Local Environment Agency North Sulawesi Province is an organization of local government to improve the welfare of the community, especially in environmental development. DLHD can not be separated from a Regional Device Organization (OPD) which will also finance office operations. This study aims to evaluate the procedure of inventory money in accordance with Permendagri No. 13 of 2006 at the Regional Environment Agency of North Sulawesi Province. The method of analysis used in this research is descriptive method. The result of the research shows that the system and procedures for applying of inventory money have not been in accordance with Permendagri. 13 of 2006 on the management of local finance, this is because there are still some procedures and documents - documents that are not suitable and not attached. preferably in the implementation of procedures and documents used in accordance with applicable regulations of Permendagri No. 13 of 2006, as a form of compliance and compliance with prevailing regulations and improving the duties and responsibilities in the system and procedures of money supply at the Regional Environment Agency of North Sulawesi Province.Keywords: System and procedure, money supply, Permendagri No. 13 of 2006